Implantation of an Intraosseous Transcutaneous Amputation Prosthesis Restoring Ambulation After Amputation of the Distal Aspect of the Left Tibia in an Arabian Tahr (Arabitragus jayakari) - Golachowski, Andrzej; Al Ghabri, Masoud Rashid; Golachowska, Barbara; Al Abri, Hamood; Lubak, Marek; Sujeta, Michal (Frontiers in Veterinary Science, 2019)
Objective: An article on the acceptance of a custom designed Intraosseous Transcutaneous Amputation Prosthesis (ITAP) fitted to the left hind limb of a female Arabian tahr (Arabitragus jayakari) and the factors needed to optimize recovery, rehabilitation and successful reunion with the herd. Study Design: A Case Report. Sample Population: A 4 year old, 15kg Arabian female tahr from the Omani Mammals Breeding Centre. An implant was inserted 4 months after amputation of the hind left leg at the level of one third distal tibia. Method: The distal limb amputation was due to a trauma allowing the possibility to insert the custom designed ITAP into the tibia. 2 weeks after the surgery an exoprosthesis was attached to the limb. 3 months post implantation a myiasis complication was observed in the junction between the skin and the implant. Immediate, aggressive treatment prevented implant infection and failure. The outcome of the surgery was measured by means of subjective assessments of the limb function and radiographic examination. Results: Skin integration with the ITAP was achieved within 28 days and shortly after the attachment of the exoprosthesis the Arabian tahr exhibited no signs of discomfort whilst walking. The tahr was successfully reunited with the breeding herd. Conclusion: Application of the ITAP to the left tibia of the Arabian tahr resulted in positive functional outcomes. 6 months post-surgery observations confirmed ambulation was restored in a pain free manner. Reintroduction to the breeding group continues to ensure conservation of endangered species. Clinical Relevance: ITAP offers a viable option to restore functionality and ambulation in wildlife despite possible post amputation problems thus saving individual animals contributes to conservation and breeding programs of endangered species.